Kinerja Ombudsman RI Perwakilan Jawa Timur Sebagai Lembaga Pengawas Eksternal Pelayanan Publik - Rochmatun Rochmatun (Jurnal Administrasi Publik, 2016)
Abstract: The performance of the Ombudsman Representative For East Java External Public Services Supervisory Authority. Public service delivery in East Java is still a lot of colored maladministration practices. In 2013, East Java province ranked second after Jakarta, as most provinces receive reports / complaints of maladministration action as many as 387 reports quoted (report in 2013 ORI). Acts of maladministration is one thing that could cause the service to be less qualified. To encourage improvement of the quality of public services, it is necessary to optimum performance of the Ombudsman of the Republic of Indonesia Representatives of East Java as an external watchdog of public services. The results showed the performance of the Ombudsman of the Republic of Indonesia Representatives of East Java in 2014 seen from indicators of inputs, process, outputs and outcomes has been running well but still less than optimal. Keywords: Performance, Ombudsman RI Perwakilan Jawa Timur, External Monitoring, Public Service Abstrak: Kinerja Ombudsman RI Perwakilan Jawa Timur Sebagai Lembaga Pengawas Eksternal Pelayanan Publik. Penyelenggaraan pelayanan publik di Jawa Timur masih banyak diwarnai praktek maladministrasi. Pada tahun 2013, provinsi Jawa Timur menduduki peringkat kedua setelah D.K.I Jakarta, sebagai provinsi terbanyak menerima laporan/pengaduan tindakan maladministrasi yaitu sebanyak 387 laporan dikutip dari (laporan tahun 2013 ORI). Tindakan maladministrasi tersebut merupakan salah satu hal yang dapat menyebabkan pelayanan menjadi kurang berkualitas. Untuk mendorong peningkatan kualitas pelayanan publik, maka diperlukan kinerja yang optimal dari Ombudsman Republik Indonesia Perwakilan Jawa Timur sebagai lembaga pengawas eksternal pelayanan publik. Hasil penelitian ini menunjukkan kinerja Ombudsman Republik Indonesia Perwakilan Jawa Timur pada tahun 2014 dilihat dari indikator input, process, output dan outcomes sudah berjalan baik akan tetapi masih kurang optimal. Â  Kata kunci: Kinerja, Ombudsman Republik IndonesiaÂ  Perwakilan Jawa Timur, Pengawas Eksternal, Pelayanan Publik